Investigation of abundant treated sea sand (ATSS) with different percentages in concrete brick making ratio 1:3 - Abdul Rahman, Othman (2010)
This study is to investigate the Abundant Treated Sea Sand (ATSS) with different percentages as material replacing in concrete brick making ratio 1:3. The abundant means that it is supplies are more than sufficient. By relating to this study, the ATSS is same as normal sea sand but it was located far away from sea water exposure. The field of studies covers crucial parameters in determining the flexural and drying shrinkage. A total of 200 ATSS concrete bricks with dimensions of 225 mm in length, 105 mm in width, and 75 mm in depth were prepared and been divided into two group with an equal numbers according to different type of testing. Every of 100 ATSS concrete brick in each of the test had five different replacements of ATSS percentages. There were 20%, 15%, 10%, 5% and 0% as the control mixture. All the samples were only cured under water curing for 7 and 28 days before testing. The water to cement ratio of 0.40 and cement to aggregates ratio 1:3 were applied to all of the sample mixtures. In accordance to the drying shrinkage testing, the 10% ATSS mixture shows the highest drying shrinkage strain compared to other mixture at indoor condition while 0% ATSS mixture shows the greatest drying shrinkage strain reading than other mixture at outdoor condition. By according to the BS 6073, it requires 0.65 MJa as a minimum flexural strength for the building materials to be used in structural applications. The final result representated that the control sample did not achieved the minimum flexural strength and the ATSS mixtures also did not meet or exceed the flexural strength of control mixtures. The study finally demonstrated that the period of abundant sea sand treated must be extended due to get the lower chloride content.